Qualitative Study of Elderly Social Activities During the Pandemic in Matahora Village - Lestari acts; Tutik Nushah (Journal for Research in Public Health, 2022)
The elderly group (elderly) is one of the groups that has a higher risk of being infected with the coronavirus. Victims of infection and death due to Covid-19 are increasing every day. The elderly group is a group that is vulnerable to contracting Covid 19, this is due to a decrease in body immunity,age over 65 years, chronic diseases suffered by the elderly. The increasing number of elderly is one of the challenges to maintaining the independence of the elderly so that they can continue to carry out social activities in continuing to live an active life. This research uses a qualitative descriptive study, which is a research method that utilizes qualitative data and is described in detail. regularly descriptive. This type of qualitative descriptive research is often used to analyze social events, phenomena or situations. Elderly activities at time Before the new normal era, the situation felt very limited due to restrictions on social activities. Several activities were found elderly although limited that is, social activities, religion, health services. After the new normal era of elderly activities at times After the new normal era, the situation feels better because the elderly can do more activities than in the pre-pandemic era. Found some activities Which older people do better, such as social activities, sports, religion, and health services for the elderly. Almost all elderly people do activities which are lacking. By doing regular physical activity you can maintain optimal health. The elderly have a high level of worry or are very worried about facing the Covid-19 pandemic. By carrying out physical activity programs and social and religious activities, people's health will be better.